Radiofrequency ablation as a concomitant procedure for the treatment of atrial fibrillation during cardiac surgery - Tiwari, Kaushal K; Gasbarri, Tommaso; Bevilacqua, Stefano; Jawarkar, Manish; Shah, Mausam; Doshi, Chirag; Glauber, Mattia (Journal of Kathmandu Medical College, 2019)
Atrial fibrillation is the most common type of arrhythmia with increasing burden for stroke and thromboembolic events. Medical treatment of atrial fibrillation has not shown promising results, so alternative method of treatment is emerging out. Cox-Maze procedure has been used for decades for the treatment of atrial fibrillation. Surgical treatment of atrial fibrillation with traditional Cox-Maze procedure is a complex and technically challenging procedure limiting its use in clinical practice. Recently, radiofrequency ablation is being used as a modification of Cox-Maze procedure. However, its effect in the treatment of atrial fibrillation in not reported uniformly and in large number of patients. Therefore, our aim of study was to assess the impact of concomitant radiofrequency ablation in the treatment of atrial fibrillation during cardiac surgery. We performed literature review on PubMed Central to evaluate effect of concomitant radiofrequency ablation for atrial fibrillation treatment. About 303 papers were found using the reported search, of which 15 represented suitable to fulfill our query. The authors, date, patient group, study type, relevant outcomes and results of these papers are tabulated. We conclude that radiofrequency ablation surgery of left atrium at the time of other cardiac procedures is a comparatively straightforward procedure with satisfactory freedom from atrial fibrillation, acceptable morbidity, mortality, and minor procedure related complications. Careful patients selection by sticking to the - Rule of 5, i.e. left atrial diameter less than 55 mm and atrial fibrillation duration no more than five years, is recommended to optimize the result of atrial fibrillation surgery.